The semantic problem in the phenomenon of verbal homonym: Nahjul Balagha as a model - Salman, Nasser; Hussein, Ali (Al-Adab Journal, 2025)
This research focuses on a semantic phenomenon that has become widespread in Arabic, which means that a single word can have multiple meanings, which may make this phenomenon ambiguous and seem like a problematic issue. This is contrary to what the language was created for, which is to make it clear and clear and remove ambiguity. However, in this research, we will review what would clarify this phenomenon and know its causes, as well as some of its applications in some words from the book Nahj al-Balagha, as well as noting the extent of the impact of context and other clues in determining the intended meaning of those words.